An Amyloid‐Fibril‐Based Colorimetric Nanosensor for Rapid and Sensitive Chromium(VI) Detection. Issue 12 (24th September 2013) - Leung, Wai‐Hong; Zou, Lan; Lo, Wai‐Hung; Chan, Pak‐Ho
<x xml:space="preserve">Abstract</x> Appearing with a trace! A new colorimetric nanosensor for CrVI from the amyloid fibrils of hen lysozyme has been developed (see picture). This nanosensor, which makes use of hen lysozyme fibrils as CrVI binders and acidified diphenylcarbazide (DPC) as the colorimetric probe, can specifically detect CrVI at the ppb level without sample pretreatment and the use of advanced instruments.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>